ISLAMIC COMMUNICATION AND ECOTHEOLOGY-BASED ENVIRONMENTAL CAMPAIGNS IN NORTH SULAWESI - Ali Ridho; Muhammad Anshori; Zainun Nur Hisyam Tahrus; Sahari; Muhammad Tahir Alibe (Universitas Islam Negeri Mataram, 2025)
Environmental problems in North Sulawesi show that there is a gap between the ideals of religious teachings on nature conservation and the reality of social practices that are still exploitative. The research uses a qualitative approach with in-depth interview techniques, observation, and analysis of related media content. The results of the study show that Islamic communication strategies based on theological values such as wisdom, justice, and trust have significant potential in shaping environmental ethics and ecological responsibility. This study confirms that the integration of ecotheology and Islamic Communication is not only normatively relevant, but also strategic as an analytical framework in responding to environmental crises.